1993
DOI: 10.1111/j.1365-3121.1993.tb00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Search for solar periodicities in Miocene tree ring widths

Abstract: We have analysed ring‐width records of two Miocene coniferous trees with an absolute age of 15–20 million years. Such data may reflect solar periodicities from the prehistoric past. Evidence for a main period of ∼ 12.5 years has been found. This is near the present basic solar activity period of ∼ 11 years. Other periodic components appear at 220, 150 and 53 years, respectively, which may also be related to solar variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…The observed records of the SSN periodicities from growth rings of trees from places with different climates, from satellites and 10 Be concentration in polar ice show regular mean cycles near 6, 11, 22, 52 and 90 years in different time scales [2,19,20,24,33,38,46,47,51,52,63]. These fluctuations are present in centurial and decadal time scales [36].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The observed records of the SSN periodicities from growth rings of trees from places with different climates, from satellites and 10 Be concentration in polar ice show regular mean cycles near 6, 11, 22, 52 and 90 years in different time scales [2,19,20,24,33,38,46,47,51,52,63]. These fluctuations are present in centurial and decadal time scales [36].…”
Section: Introductionmentioning
confidence: 92%
“…Tree ring data has been used to study solar activity and climate variation in the past [13,20,38,46]. The observed records of the SSN periodicities from growth rings of trees from places with different climates, from satellites and 10 Be concentration in polar ice show regular mean cycles near 6, 11, 22, 52 and 90 years in different time scales [2,19,20,24,33,38,46,47,51,52,63].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Raspopov et al (2000Raspopov et al ( , 2001 concluded that the periods of between ∼ 17 and ∼ 18 and ∼ 30 and ∼ 35 years might also be a result of solar activity nonlinear effect in atmospheric processes. Kurths et al (1993) showed that the combinations of two periods of 12.6 and 17.1 year could generate periods of 7.3 and 47.9 years as mathematical described by the following equations: (1/12.6) + (1/17.1) ∼ = 1/7.3, and (1/12.6) − (1/17.1) ∼ = 1/47.9.…”
Section: Solar Influencesmentioning
confidence: 99%
“…False rings can be produced by trees enduring short intraseasonal disturbances including drought, frost, herbivory, storm damage, ash fall and even earthquakes (Fritts 1976;Creber & Chaloner 1984;Sheppard & Jacoby 1989;Filion & Quinty 1993;Kurths et al 1993). One Korsaröd specimen bears evidence of charring without any healing response, indicating death by the time of the fire.…”
Section: Patterns Of Wood Growthmentioning
confidence: 99%